Inhibition of miR‐93‐5p promotes osteogenic differentiation in a rabbit model of trauma‐induced osteonecrosis of the femoral head. Issue 8 (16th July 2021) - Zhang, Ying; Zhuang, Zhikun; Wei, Qiushi; Li, Peifeng; Li, Jitian; Fan, Yanan; Zhang, Leilei; Hong, Zhinan; He, Wei; Wang, Haibin; Liu, Youwen; Li, Wuyin
Abstract : Trauma‐induced osteonecrosis of the femoral head (TIONFH) is characterized by femoral head collapse accompanied by degenerative changes of the hip. We previously reported that miR‐93‐5p expression is abnormally high in patients with TIONFH, but the role of miR‐93‐5p in the TIONFH process remains unclear. Herein, we investigated the role of miR‐93‐5p in TIONFH in a rabbit model. Bone marrow mesenchymal stem cells (BMSCs) were used for both in vivo and in vitro experiments. A rabbit model of TIONFH was injected with BMSCs transfected with miR‐93‐5p inhibitor. In addition, both an miR‐93‐5p mimic and negative control were transfected into BMSCs. Expression of miR‐93‐5p was significantly increased in the model group compared with control samples. An miR‐93‐5p inhibitor induced the expression of bone morphogenetic protein 2 (BMP‐2) and alkaline phosphatase. Furthermore, expression of osteogenesis‐related markers (BMP‐2, secreted phosphoprotein 1, RUNX family transcription factor 2 and Osterix) was higher in the miR‐93‐5p inhibitor group, as revealed by quantitative PCR and western blotting. In addition, in vitro experimentation revealed that an miR‐93‐5p mimic decreased BMP‐2 and TNF receptor superfamily member 11b expression, but increased receptor activator of nuclear factor‐kappaB ligand expression. In summary, the miR‐93‐5p inhibitor could promote osteogenic differentiation by increasing BMP‐2 expression during the development of TIONFH. Thus, miR‐93‐5p may have potential as a therapeutic target for TIONF treatment. Abstract : Here, we investigated the role of miR‐93‐5p in a rabbit trauma‐induced osteonecrosis of the femoral head model and in vitro using bone marrow mesenchymal stem cells. In vivo, miR‐93‐5p expression was significantly increased in the model group, and its inhibition resulted in an increase in the level of osteogenesis‐related markers. In vitro, application of a miR‐93‐5p mimic led to a decrease in bone morphogenetic protein 2 expression. Thus, inhibition of miR‐93‐5p may promote osteogenic differentiation in trauma‐induced osteonecrosis of the femoral head.